A review on composite materials for offshore structures - Setvati, M.R. (American Society of Mechanical Engineers (ASME), 2014)
Research into advanced composite materials for offshore structures is growing due to factors such as new challenges in extreme environments, contaminated contexts (chemical, biological) and increasing awareness of earthquake risks. Advances in theory and practice of composites technology have modified the general perception of offshore structures. This paper provided an introduction to composite material and reviewed the application of composites in offshore structures. This survey focused on (1) composites, especially FRP, for repairing offshore structures and also (2) fire protection of composites in offshore structures. Various national and international research projects on uses of composites for marine structures either ongoing or completed during last decades summarized. Future environmental issues considered and eco-friendly sustainable composite suggested and forecasted for new generation of offshore structures. Copyright Â© 2014 by ASME.